1998
DOI: 10.1074/jbc.273.25.15329
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Inositol Hexakisphosphate Interaction with Human Oxyhemoglobin

Abstract: , which are located in the ␤ 1 ␤ 2 dyad axis, where they have been also proposed to interact with 2,3-diphosphoglycerate, whereas the third group does not appear easily identifiable. Calorimetric measurements of the heat associated with IHP binding at different pH values over the same range indicate that IHP binding is mostly enthalpy-driven at pH < 7 and mostly entropydriven at pH > 7.Human hemoglobin (Hb) 1 is functionally modulated by several non-heme ligands, such as organic phosphates (i.e. 2,3-diphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…All phosphate groups were considered to be completely charged. In fact, the InsP 6 charge in solution, at pH 7.5, is < 28 [19], whereas when it is bound to Hb the pK a values of its phosphate groups decrease [20,21]. The InsP 6 model obtained was identical to that reported by Arnone and Perutz [20] in the crystallographic structure of the deoxy-Hb A±InsP 6 complex.…”
Section: Molecular Modellingsupporting
confidence: 72%
See 2 more Smart Citations
“…All phosphate groups were considered to be completely charged. In fact, the InsP 6 charge in solution, at pH 7.5, is < 28 [19], whereas when it is bound to Hb the pK a values of its phosphate groups decrease [20,21]. The InsP 6 model obtained was identical to that reported by Arnone and Perutz [20] in the crystallographic structure of the deoxy-Hb A±InsP 6 complex.…”
Section: Molecular Modellingsupporting
confidence: 72%
“…6. The results obtained at different temperatures were used to calculate the DH values which, expressed as kcal´mol 21 oxygen, were 210.4 and 210.2 for K T , and 210.6 and 211.1 for K R , for Hb 1 and Hb , respectively. These data suggest that temperature affects the binding of oxygen to the first and to the fourth site to a similar extent in the two Hbs.…”
Section: Q Febs 2000mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, free Glc-1,6-P 2 may represent only a small fraction of total Glc-1,6-P 2 in erythrocytes due to binding to hemoglobin. Hemoglobin is indeed known to bind avidly multiply charged phosphate esters such as 2,3-bisphosphoglycerate and inositol pentakisphosphate (33). It is therefore likely that it will also bind with great affinity bisphosphate esters such as Glc-1,6-P 2 .…”
Section: Discussionmentioning
confidence: 99%
“…ITC is the only technique that allows the direct thermodynamic analysis of biomolecular interactions, providing the binding constant and stoichiometry in addition to the enthalpy and entropy of binding. Several ITC studies showed that electrostatic binding is usually driven by enthalpy (3,26,31,41,50). However, it is important to point out that the calorimetric enthalpy is actually a sum of all the heat effects, endothermic and exothermic, taking place during the interaction.…”
Section: Vol 76 2002 Membrane Recognition By Vsv G Protein 3761mentioning
confidence: 99%